Coating of Intestinal Anastomoses for Prevention of Postoperative Leakage: A Systematic Review and Meta-Analysis - Cira, Kamacay; Stocker, Felix; Reischl, Stefan; Obermeier, Andreas; Friess, Helmut; Burgkart, Rainer; Neumann, Philipp-Alexander (Frontiers in Surgery, 2022)
Background: For several decades, scientific efforts have been taken to develop strategies and medical aids for reduction of anastomotic complications after intestinal surgery. Still, anastomotic leakage represents a frequently occurring postoperative complication with serious consequences on health, quality of life and economic aspects. Approaches using collagen and/or fibrin-based sealants to cover intestinal anastomoses have shown promising effects towards leak reduction, however they have not reached routine use yet. To assess effects of covering intestinal anastomoses with collagen and/or fibrin-based sealants on postoperative leakage, a systematic review and meta-analysis was conducted. Method: We searched PubMed, Web of Science, Cochrane Library and Scopus (1964 – 01/17/2022) to identify studies, investigating effects of coating any intestinal anastomoses with collagen and/or fibrin-based sealants on postoperative anastomotic leakage, reoperation rates, Clavien-Dindo major complication, mortality and hospitalization length. Pooled odds ratio (OR) with 95% confidence intervals (CI) were calculated. Results: Overall, 15 studies (5 randomized controlled trials; 3 non-randomized intervention studies, 6 observational cohort studies) examining 1387 patients in the intervention group and 2243 in the control group were included. Using fixed-effects meta-analysis (I2 <50%), patients with coated intestinal anastomoses presented significantly lower anastomotic leakage rates (OR = 0.37; 95% (CI) 0.27–0.52; p <0.00001); reoperation rates (OR, 0.21; 95% CI, 0.10 – 0.47; p = 0.0001) and Clavien-Dindo major complication rates (OR, 0.54; 95% CI, 0.35–0.84; p = 0.006) in comparison to controls, with results remaining stable in sensitivity and subgroup analyses (stratified by study design, age group, intervention used, location of anastomoses and indication for surgery). Length of hospitalization was significantly shorter in the intervention group (weighted mean difference (WMD, -1.96; 95% CI: -3.21, -0.71; p = 0.002) using random-effects model meta-analysis (I2 ≥50%), especially for patients with surgery of upper gastrointestinal malignancy (WMD, -4.94; 95% CI: -7.98, -1.90; p=0.001). Conclusion: Application of collagen-based laminar biomaterials or fibrin sealants on intestinal anastomoses can significantly reduce postoperative rates of anastomotic leakage and its sequelae. Coating of intestinal anastomoses could be a step towards an effective and sustainable leak prevention. To assess the validity and robustness of these findings, further clinical studies need to be conducted.